Effect of vitamin D supplementation on bone mineral density in people with low risk of osteoporosis - Kacper Pajor; Justyna Szpyt; Anna Lubkowska (Kazimierz Wielki University, 2019)
Introduction. With the increasing number of reports of vitamin D3 deficiency, public awareness of this vitamin is increasing. Therefore, more and more people are choosing to supplement it. One of the main results expected is increase of bone strength. Vitamin D3 intake and its effect on bone mineral density are well studied in groups at increased risk for osteoporosis, but there is insufficient data on the effect of vitamin D3 supplementation on bone mineral density in people at low risk of osteoporosis. Aim of study. The aim of the study was to examine the effect of vitamin D3 supplementation on bone mineral density in people with low risk of developing osteoporosis. Material and methods. The study involved 76 people (39 women and 37 men) aged 20-43. To examine bone composition and mineral density dual-energy X-ray absorptiometry method has been used (Hologic Inc., USA). Respondents received also surveys regarding the presence of osteoporosis risk factors and vitamin D3 supplementation. Results. In the study group, 46.1% regularly supplements vitamin D3, of which 40% are women and 60% are men. There were no statistically significant differences (p = 0.1753) between bone mineral density values in people regularly supplementing vitamin D3 compared to people not taking vitamin D3. Conclusions. Vitamin D3 supplementation may not have a significant effect on bone mineral density in people who have a low risk of osteoporosis. Vitamin D3 supplementation is one of the most common supplements also among people with low risk of osteoporosis.